2021
DOI: 10.3390/jcm10184092
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Measure of Patellar Tendon Thickness Based on Ultrasonography and MRI in University Athletes

Abstract: Ultrasonography and MRI are used for imaging evaluation of patellar tendinopathy, and “thickening of the tendon” is known as one of the characteristic findings. However, there are no evidence-based quantitative criteria to help evaluate this phenomenon. The purpose of this study was to investigate an objective measure of patellar tendon thickness. Patellar tendon thickness was evaluated in 65 elite university athletes using both ultrasonography and MRI. The relationship between tendon thickness and clinical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…Nishida et al described in their work the PTTmid as 4.6 ± 0.9 mm (p = 0.005), while in this study, it was 5.34 ± 1.54 mm, which coincided with the observation that in this tendon section, there was also a significantly larger value for the PT. The trend of a significantly thickened tendon was also seen in the PTTdistal in this study, but this contradicts the observations of Nishida et al who did not show any significant differences in the distal portion (p = 0.67) [16]. It would be beneficial to measure the patellar tendon thickness divided into PTTprox, PTTmid and PTTdistal by MRI in further studies to generate clear cut-off values.…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…Nishida et al described in their work the PTTmid as 4.6 ± 0.9 mm (p = 0.005), while in this study, it was 5.34 ± 1.54 mm, which coincided with the observation that in this tendon section, there was also a significantly larger value for the PT. The trend of a significantly thickened tendon was also seen in the PTTdistal in this study, but this contradicts the observations of Nishida et al who did not show any significant differences in the distal portion (p = 0.67) [16]. It would be beneficial to measure the patellar tendon thickness divided into PTTprox, PTTmid and PTTdistal by MRI in further studies to generate clear cut-off values.…”
Section: Discussioncontrasting
confidence: 88%
“…In this study, the mean value of the control group for PTTprox was 4.76 ± 0.97 (2.84-7.02). The results of Nishida et al showed that PTT thicker than 7.0 mm has clinical significance on both US and MRI [16]. In this study, patients with PT had a PTTprox of 6.83 ± 2.36 (3.67-13.59).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations